Digitalisasi Koperasi Merah Putih dan Sistem Informasi Berbasis Web Untuk Meningkatkan Partisipasi Program Keluarga Berkualitas di Desa Tiohu - Rosbin Pakaya; Nur Oktavin Idris; Fuad Pontoiyo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Optimization of participation in the quality family program and the digitalization of the Merah Putih cooperative in Tiohu Village is the main focus of this community service, based on the challenge of low public participation due to limited access to information and the still manual recording process. This study aims to develop a web-based information system to support the quality family program while also digitizing the cooperative, in order to sustainably increase community involvement in the village’s social and economic services. The methodology applied includes needs identification, system design and development using the PHP programming language and MySQL database, followed by socialization, participatory training, and monitoring and evaluation. The results show that the implemented digital system has succeeded in accelerating access to information, strengthening the service functions of the quality family program, and encouraging the cooperative’s economic independence. Implicitly, this activity contributes to the development of a digital technology-based empowerment model that is adaptive to the local context, while also providing a tangible impact in improving management efficiency and community participation